Rewitalizacja jako zadanie rozwojowe - Błajet, Piotr (Studia Edukacyjne, 2020)
The article focuses on healthy longevity. The starting point is the assumption that a long and healthy life, much as it is genetically– and environmentally-dependent, is likewise related to one’s lifestyle. The text tries to indicate which elements of the lifestyle contribute to healthy longevity. To this end, the article reviews approaches and theoretical concepts on healthy ageing and provides empirical data gathered in longevity zones worldwide, called the Blue Zones by National Geographic researchers. Analysis confirmedK. Wisniewska-Roszkowska’s observations that a long and healthy life depends on a proper diet, physical activity and care for mental health. The author has suggested that the obe-sity index should be an indicator of ageing pathology.